PENYULUHAN DAN PELATIHAN PEMBUATAN PRODUK NUTRASETIKAL IE BU PEUDAH SEBAGAI ANTIDIABETES DI DESA MEURANDEH, LANGSA, ACEH - Rahmazani, Intan; Junidil Asna, Intan; Nabilla, Ulya; Ilman Navia, Zidni (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
Ie bu peudah is a traditional Acehnese dish made with 44 different leaf and spice species. This spicy porridge is typically consumed during Ramadan since it is thought to improve the body's endurance after fasting all day. The raw components used to make these nutraceutical products are known to offer anti-diabetic properties. This community service project intends to provide knowledge and training on how to make nutraceutical goods, which can help diabetics maintain their health and prevent future issues. This community service project is carried out in Meurandeh Village, Langsa City, using a community empowerment strategy that consists of three stages: counseling, practice, and evaluation monitoring. According to the findings of this exercise, 80% of the general population.